The Effectiveness of the Role of Internal Control System in the Preparation of Regional Financial Statements - Khikmatul Islah; Cundo Harimurti; Miroslaw Matyja (Ilomata International Journal of Social Science, 2022)
The existence of regional autonomy supports changes in various sectors, including changes in financial management. This is evidenced by the birth of three packages of laws in the field of state finance, namely: Law Number 17 of 2003 concerning State Finance; Law Number 1 of 2004 concerning the State Treasury; and Law Number 15 of 2004 concerning Examination of the Management and Accountability of State Finances. These three packages of laws regulate the management of state finances more democratically and regulate sanctions for managers of state finances. To support the implementation of regional autonomy in financial management, it is necessary to anticipate deviations in the preparation of financial statements. This study aimed to analyze the Effectiveness of the Role of the Internal Control System in the Preparation of Regional Financial Reports. The research approach is a descriptive qualitative approach. The method of analysis uses a literature study. The study results on the Effectiveness of the Role of the Internal Control System in the Preparation of Regional Financial Reports indicate that the internal control system has an effective role in preparing regional financial reports. But this internal control system cannot be said to be perfect. The internal control system still has limitations because this control system is a form of prevention, reduction, improvement of deviations.